ARTIFICIAL INTELLIGENCE AND ROBOTICS: THEORETICAL AND LEGAL PROBLEMS OF DIFFERENTIATION OF THE CONCEPTUAL APPARATUS - Begishev, I.R.; Khisamova, Z.I. (Bulletin of Udmurt University. Series Economics and Law, 2020)
A distinction is made between such concepts as “robotics” and “artificial intelligence”. These categories are not only multi-volume, but also semantically non-falling. After analyzing the conceptual apparatus of these terms, we can conclude that, in contrast to the first, the second is characterized by the presence of “intelligence”, self-development, etc. However, when discussing the legal status of robots and artificial intelligence, most scientists allow confusion of concepts, making attempts to justify the need to confer a legal status on robots, and not artificial intelligence. The question of considering robots and artificial intelligence as subjects of law, in principle, can be considered justified. However, it is premature to consider this issue, but the topic will not lose its relevance in the future. Among the currently available approaches to the consideration of robots and artificial intelligence as subjects of law, the path constructed by analogy with a legal entity from the point of view of the theory of fiction is the most justified. Approaches that offer to justify the legal personality of robots and artificial intelligence, taking into account the essence of animate subjects who have a real, and not just a formal legal will, will be developed only after the development of digital technologies reaches an objectively high level. When implementing these approaches, it is necessary to take into account the existence of legal and economic validity and social conditionality, as well as a possible theoretical and legal problem, the essence of which is as follows: if new legal entities with legal personality are introduced, the level of responsibility of professional market participants may decrease.